Mulheres, conquistando espaços dentro do Instituto Federal de Educação Ciência e Tecnologia do Ceará (IFCE)-Campus Iguatu - Oliveira, Silvelena Alves de Araújo (2015)
The goal of this study is to evaluate the Mulheres Mil (Thousand Women) program as a Public Policy developed within the Instituto Federal de Educação Ciência e Tecnologia (IFCE) [Federal Institute of Education, Science and Technology] on the Iguatu Campus. The Mulheres Mil Program brings not only professional qualification as a proposal but also the recognition of the importance of these women in their families and communities. The question therefore is whether this goal is in fact accomplished, specifically in the Bread Making course promoted by the IFCE Iguatu campus. What significant changes could be perceived in the life of these women after the end of the course? What changes happened related to improvement of income or insertion in the work market? Was there a quest for autonomy or improvement of self-esteem and well being due to the professionalization? The answers to these questions arise from the observation of the participants of the Program of the Bread Making Course, that is, 50 women dwellers of the João Paulo II neighborhood, whose profile can be delimited as women of little schooling, responsibility for managing the home, including the financial management, most of them included in social programs such as the Family Grant and who still bring, even in the midst of this reality, the desire to take advantage of the opportunities which arise. With regard to the changes which the program brought into their lives, all of them consider the impact to be positive, mainly, because if awakened in them the desire to learn more and do new courses. With regard to those who finished the course, there still have not been positive results with regard to insertion in the formal work market. Most of them sought to enroll in new courses and one of them opened up her own business. They complained, with regard to the course, that there should be an intensification of the practical classes, but seemed to be satisfied with the results and reiterate the importance of the course in various aspects: learning, reflection about themselves, about life and the community. Finally, one can summarize that the results of the program have generated the expected impact, not eliminating, however, the possibility of improvement which always exists.